PENGARUH PEMAHAMAN TENTANG BAGI HASIL DAN BUNGA TERHADAP MINAT MENJADI NASABAH BANK SYARIAH (STUDI KASUS MAHASISWA JURUSAN AKUNTANSI POLITEKNIK NEGERI SAMARINDA) - Angga Kusumah; Sailawati Sailawati (Jurnal Eksis, 2020)
The purpose of this study was to analyze the effect of understanding Islamic banking students on profit sharing and interest on the interest in becoming a customer of Islamic banks. The sample taken was 47 students majoring in the Accounting Department of Finance and Banking, Politeknik Negeri Samarinda Class of 2017. The sampling technique used a probability sampling method with a cluster sampling technique. In processing the data, this study uses the SPSS 20 program. This study uses multiple linear analysis. This analysis is used to examine the relationship between two or more independent variables and the dependent variable. The results show that the variable understanding of profit sharing and understanding of interest simultaneously has a positive and significant effect on the interest in becoming a customer of Islamic banks. Of the two variables, it can be stated partially that they have a positive and significant effect on the interest in becoming a customer of Islamic banks.Keywords : understanding profit sharing, understanding interest, interest in becoming a customer of Islamic banks